2014
DOI: 10.31910/rudca.v17.n2.2014.242
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of purple passion fruit (Passiflora edulis Sims) growth under ecological conditions of the Colombian lower montane rain forest

Abstract: High-Andean fruits are considered important for their domestic consumption and exportation potential. Among them, purple passion fruit (Passiflora edulis Sims) is largely accepted in European markets. However, its short shelf life, worsened with the limited knowledge of the species lead to rapid fruit deterioration. An important contribution to the development of this crop is fruit growth mathematical modeling, which allows estimating harvest related issues, in order to define applicable agronomic management p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
3
0
4
Order By: Relevance
“…As in our study, Franco et al (2014) used RGR values to determine that the fruits of Passiflora edulis have three growth phases with periods and duration that differ from those found for P. tripartita in our work, since despite their relationship, each species is genetically different and grows in different climates. Franco et al (2014) mention that the identified phases for fruit growth are related to the development of the seeds of P. edulis, and in addition, in the first 35 d after flowering an expansion of the intercellular spaces occurs within the fruits of P. edulis. Beadle (1993) mentions that, in general, fruit growth can be represented by curves that depict absolute and relative growth rates, allowing one to forecast fruit size and growth, which facilitates the optimization of crop management.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…As in our study, Franco et al (2014) used RGR values to determine that the fruits of Passiflora edulis have three growth phases with periods and duration that differ from those found for P. tripartita in our work, since despite their relationship, each species is genetically different and grows in different climates. Franco et al (2014) mention that the identified phases for fruit growth are related to the development of the seeds of P. edulis, and in addition, in the first 35 d after flowering an expansion of the intercellular spaces occurs within the fruits of P. edulis. Beadle (1993) mentions that, in general, fruit growth can be represented by curves that depict absolute and relative growth rates, allowing one to forecast fruit size and growth, which facilitates the optimization of crop management.…”
Section: Resultsmentioning
confidence: 98%
“…As in the present work, Arjona et al (1991) found a sigmoid curve for the diameter of the fruits of Passiflora edulis and P. incarnata. Franco et al (2014) also report that the growth dynamics of the polar and longitudinal diameter of P. edulis fruits are sigmoid. Stikić et al (2015) mention that the dynamics of fruit growth usually occurs in sigmoid form, in which the increase in fruit diameter is represented as a function of time.…”
Section: Casierramentioning
confidence: 85%
See 1 more Smart Citation
“…La pasiflora tiene presente muchos metabolitos secundarios como fenoles, leucoantocianidinas flavonoides, triterpenos y alcaloides, todos presentes en la cáscara, y que tienen gran relación con la actividad antioxidante del fruto es sus procesos de maduración (Franco, 2013). En sus jugos, la gulupa tiene un gran potencial de actividad antioxidante debido a los contenidos de ácido ascórbico y carotenoides que aumentan en su proceso de maduración y poscosecha, el contenido de neutralización del Radical ABTS•+ está entre los 300 y 400 µmol Trolox/100 g de fruto fresco, fenoles entre 200 y 300 mg de ácido gálico/100 g fruta y DPPH entre 90 y 100 de µmol Trolox/100 g de fruto fresco y FRAP de 36 a 40 mg ácido ascórbico/100 g muestra (Franco et al, 2014;Moreno et al, 2014;Rudnicki, 2007).…”
Section: Capacidad Antioxidanteunclassified
“…Despite its importance, the purple passion fruit remains poorly investigated agronomically as well especially compared to the yellow passion fruit, which is more prevalent throughout tropical lowland areas of Brazil, Central America, and the Caribbean (Cerqueira et al, 2014;Marostega et al, 2017). Although purple passion fruit is now found in the highland tropics of Africa and sub-tropical regions, its original range was in mid to higher altitude elevations of the Andes (Franco et al, 2014).…”
Section: Introductionmentioning
confidence: 99%